Scale Economics, Market Power, and Pricing Behavior Evidence from German Newspaper and Magazine Publishing - Erik Lehmann; Jürgen Weigand (Universität Rostock, Institut für Volkswirtschaftslehre, 1998)
The anomalous inverse concentration-price relationship observed by some researchers in the newspaper market has been attributed to scale economies. In this paper we suggest that the newspaper's (or magazine's) double-product feature (i.e., news supplied to readers and advertising space supplied to advertisers) is the main source of this anomaly. In a simple oligopoly model it is shown how a profit-maximizing publisher takes advantage of that feature. Empirically an inverse concentration-price relationship may arise if double-product pricing is not controlled for. Regression results for a cross-section of 222 German Newspapers and magazines corroborate the theoretical implications.
Keywords: D4; L13; L82; 330; Scale Economics; Advertising; Concentration; Pricing Behavior; Presseverlag; Zeitschriftenverlag; Struktur-Performance-Modell; Oligopol; Betriebliche Preispolitik; Skalenertrag; Theorie